2015
DOI: 10.1186/s12863-015-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of host genetics on outcome of tuberculosis infection due to differences in killer immunoglobulin-like receptor gene frequencies and haplotypes

Abstract: BackgroundOutcome of Mycobacterium tuberculosis (Mtb) infection is affected by virulence of the infecting strain of Mtb, host environment, co-morbidities, and the genetic composition of the host, specifically the presence or absence of genes involved in immune responses/regulation. It is hypothesized that specific killer immunoglobulin-like receptor (KIR) genes may be associated with Mtb infection and clinical outcome. This cross-sectional study examined the KIR gene frequencies, profiles, and haplotypes of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…In addition, candidates for diseases that could have affected KhoeSan KIR diversity are measles, smallpox and TB, which were introduced to the KhoeSan during the last 250 years by Europeans (102). A case for the role of KIR in NK cell mediated control of TB is being made (103, 104). Supporting this hypothesis, KhoeSan ancestry is associated with increased risk of developing active TB (102), and with the role of activating KIR in preventing that development (105).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, candidates for diseases that could have affected KhoeSan KIR diversity are measles, smallpox and TB, which were introduced to the KhoeSan during the last 250 years by Europeans (102). A case for the role of KIR in NK cell mediated control of TB is being made (103, 104). Supporting this hypothesis, KhoeSan ancestry is associated with increased risk of developing active TB (102), and with the role of activating KIR in preventing that development (105).…”
Section: Discussionmentioning
confidence: 99%
“…As our study indicated that individuals with the aKIR gene 3DS1 and with 5 or more aKIRs, were protected against TB, we show an essential role of aKIRs in TB disease, which could be as a result of altered cytolytic activity of NK cells to M. tuberculosis infected cells. Previous studies have identified associations between KIRs and TB disease outcome [6,8], where NK cells were shown to control M. tuberculosis infection. Individuals with a greater number of aKIRs had a greater NK cell response to mycobacterial infection due to an increased IFN-g response [6] and a lack Table 1 KIR gene profiles and their caseecontrol association data for susceptibility to TB in the SAC population.…”
Section: Discussionmentioning
confidence: 99%
“…Many KIR genes and KIR-HLA-B/KIR-HLA-C pairs have been associated with distinct outcomes in the context of HIV-1 infection [6,[11][12][13][14]. In the same way, genetic studies involving protection or susceptibility to pulmonary tuberculosis have also highlighted the role of HLA-B and KIR genes, as well as KIR + HLA-C pairs [5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%